HIC2 is a novel dosage-dependent regulator of cardiac development located within the distal 22q11 deletion syndrome region. - Dykes, I; van Bueren, K; Ashmore, R; Floss, T; Wurst, W; Szumska, D; Bhattacharya, S; Scambler, P (Lippincott Williams and Wilkins, 2014)
RATIONALE: 22q11 deletion syndrome arises from recombination between low-copy repeats on chromosome 22. Typical deletions result in hemizygosity for TBX1 associated with congenital cardiovascular disease. Deletions distal to the typically deleted region result in a similar cardiac phenotype but lack in extracardiac features of the syndrome, suggesting that a second haploinsufficient gene maps to this interval. OBJECTIVE: The transcription factor HIC2 is lost in most distal deletions, as well as in a minority of typical deletions. We used mouse models to test the hypothesis that HIC2 hemizygosity causes congenital heart disease. METHODS AND RESULTS: We created a genetrap mouse allele of Hic2. The genetrap reporter was expressed in the heart throughout the key stages of cardiac morphogenesis. Homozygosity for the genetrap allele was embryonic lethal before embryonic day E10.5, whereas the heterozygous condition exhibited a partially penetrant late lethality. One third of heterozygous embryos had a cardiac phenotype. MRI demonstrated a ventricular septal defect with over-riding aorta. Conditional targeting indicated a requirement for Hic2 within the Nkx2.5+ and Mesp1+ cardiovascular progenitor lineages. Microarray analysis revealed increased expression of Bmp10. CONCLUSIONS: Our results demonstrate a novel role for Hic2 in cardiac development. Hic2 is the first gene within the distal 22q11 interval to have a demonstrated haploinsufficient cardiac phenotype in mice. Together our data suggest that HIC2 haploinsufficiency likely contributes to the cardiac defects seen in distal 22q11 deletion syndrome.